The Effect of Non-availability of the Title to Property on the Security Mortgage Contract A Comparative Analytical Study - Al-Adwan, Mohammed khair M.; Al-Shbool, 2. Nathem; Al shawabkeh, Mahmoud (Journal of Ecohumanism, 2024)
Purpose: Determine the impact of the debtor’s non-ownership of the mortgaged money on the validity and enforceability of the mortgage contract in accordance with applicable legislation. Theoretical reference: This research relies on the Jordanian Civil Law as the main reference, with comparison to other legislation such as Egyptian and French, which means determining the position of the Jordanian judiciary on the main problem in the research. Method: This study is considered a descriptive, analytical, comparative study, in which researchers will rely on describing the theoretical problem in legislation, analyzing texts, and comparing that with the laws referred to in the study. Results and Conclusion: The main conclusion is the security mortgage whose title to property is expected may be void if its subject was on a future property, and it may be also suspended if the ownership of the property is dependent on the obtaining of a certain condition. Implications of research: The security mortgage issued by the mortgagor's agent is considered valid as long as the agency is valid, and the security mortgage is considered issued on the property of others if the validity of the agency is invalid, so that the agent then does not have authority, or jurisdiction derived from the principal, to conclude the security mortgage. Originality/value: The value of the research is concentrated in its discussion of a practical issue that the legislator has not decided, and which has opened the door to jurisprudential and judicial diligence, despite its great importance, given that ownership of the mortgaged property is close to being considered a condition for the validity of the mortgage.